Intelligent E-commerce logistics platform using hybrid agent based approach. (June 2019) - Barenji, Ali Vatankhah; Wang, W.M.; Li, Zhi; Guerra-Zubiaga, David A.
Highlights: Intelligent E-commerce logistics platform was explained and the main problems related to dynamic scheduling and control system as defined in the detail. A hybrid-based agent platform was proposed and implemented in the case study. Two types of communication mechanism were proposed for improving data integration on the system. Abstract: This paper proposes a hybrid agent-based approach for the scheduling and synchronization of e-commerce logistics parks (EcLP). This is accomplished by integrating intelligent distribution centers within the e-commerce environment. The proposed platform has been developed based on an agent technology, which not only serves for decentralization and synchronization purposes but also it has been optimized for the transportation and logistics of the overall system. Moreover, mobile agent-based communication mechanisms between the hardware agents and the software agents were developed, and the proposed hybrid agent-based platform was implemented and tested based on a case study. Following this, the results were compared to a conventional system based on four main indicators.